22=2(2t-6)

Simple and best practice solution for 22=2(2t-6) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 22=2(2t-6) equation:



22=2(2t-6)
We move all terms to the left:
22-(2(2t-6))=0
We calculate terms in parentheses: -(2(2t-6)), so:
2(2t-6)
We multiply parentheses
4t-12
Back to the equation:
-(4t-12)
We get rid of parentheses
-4t+12+22=0
We add all the numbers together, and all the variables
-4t+34=0
We move all terms containing t to the left, all other terms to the right
-4t=-34
t=-34/-4
t=8+1/2

See similar equations:

| 7b+12=19 | | y/11=26 | | 500(x−3)=5,​000 | | 22=2(2t-6 | | 2m+6m-3m=40 | | 4(x-2)+5=-2x+9 | | 4x+15+7=94 | | 5x^-200x-100=0 | | 120=3(4x+8) | | k/3+7=28 | | 1/4x+41/8+1/2x=5/8 | | 2.2-5=9.8=3m | | x}{8}=-4 | | 6.5x+8-8x=-5x-5 | | 30c/30=-143/30 | | 5m-2m+3=-18 | | 0=-(4+x) | | 9=4s+13 | | 2x2+6x−216=0 | | 3x+15=7x+94 | | -1.3=-0.8+c/3.4 | | 15x+5=16x+6 | | 25=-n/2 | | 5+7(a-2)=-37 | | 7x+3x+15=94 | | 118=-5(4+7x)+7 | | 10k+40=7k+67 | | (-4z+4)=(4z+4) | | -4(x-6)-2x=-6x+25 | | -19+15+17t=20+15t | | X+30+3x+40=180 | | 5(5c+6)=25+30c |

Equations solver categories